The ghost of glaberrima: descriptions of two new Leiopathes species - Jeremy Horowitz; Dennis M. Opresko; Declan Morrissey; Victoria Polit; Heather C. Shull; Teresa Cerqueira; Luke J. McCartin; Samuel A. Vohsen; Marina Carreiro-Silva; Andrea M. Quattrini (Coral Reefs, 2026)
Two new species of black coral are described herein: Leiopathes dumosa nov. sp. and Leiopathes brugleri nov. sp. Samples were collected between depths of 244 and 617 m on the North American continental slope between Texas and Florida, USA, and recognized in the family Leiopathidae Haeckel, 1896. L. dumosa nov. sp. is characterized by short stems and short branches forming bush-like colonies (usually less than 1 m tall and 0.25 m wide), with branchlets 1.5–2 cm in length, polyps 1–1.6 mm in transverse diameter, and spines 0.02–0.04 mm tall. L. brugleri nov. sp. is characterized by short stems and long branches forming tree-like colonies (can exceed 2 m in width and height), with branchlets 8–10 cm in length, polyps 2 mm in transverse diameter, and spines 0.03–0.06 mm tall. Additionally, we revise the description of Leiopathes glaberrima (Esper 1792) to facilitate morphological comparison with the new species described herein and to support future studies on Leiopathidae. Historically, Leiopathes from this region were misidentified as L. glaberrima (Esper 1792). Our findings reveal that the North American continental slope between Texas and Florida harbors at least two distinct species of Leiopathes and we have yet to collect L. glaberrima in the region. Following the Deepwater Horizon oil spill in 2010, Leiopathes was designated as a priority taxon for regional conservation and management by the National Oceanic and Atmospheric Administration, prompting restoration efforts and population studies. The discovery of multiple species distinct from L. glaberrima has major implications for the success of ongoing and future conservation and restoration strategies. ZooBank registration: urn:lsid:zoobank.org:pub:E3ECAAD7-B68E-4E53-BE99-7C138F44CA43.